Hedyotis zhihaoana (Rubiaceae), a new species from Yunnan, Southwest China - Liu, Xiao-Lan; Li, Yu-Ran; Yang, Feng; Wang, Huan-Chong (Phytotaxa, 2020)
Hedyotis zhihaoana Huan C. Wang & Xiao Lan Liu, a new species in Rubiaceae, is described and illustrated, and its phylogenetic placement within Hedyotis is elucidated using ITS sequnences. The new species was found in western Yunnan, Southwest China. It morphologically resembles H. acutangula, but clearly differs from the latter by its amplexicaul leaf base, broadly triangular stipules usually ca. 1.0 mm long, and densely with small brown glands, subsessile flower pedicels ca. 0.5–2 mm long, and sepals lanceolate to linear, 1–2 mm long.